The favored daughter one woman's fight to lead Afghanistan into the future - Koofi, Fawzia 1975-; Ghouri, Nadene 1975- (Palgrave Macmillan, 2012)
The nineteenth daughter of a local village leader in rural Afghanistan, Fawzia Koofi was left to die in the sun after birth by her mother. But she survived, and perseverance in the face of extreme hardship has defined her life ever since. Despite the abuse of her family, the exploitative Russian and Taliban regimes, the murders of her father, brother, and husband, and numerous attempts on her life, she rose above her fate to becoming the first Afghani woman Parliament speaker. Here, she shares her amazing story, punctuated by a series of poignant letters she wrote to her two daughters before each political trip--letters describing the future and freedoms she dreamed of for them and for all the women of Afghanistan. Today, Koofi is one of the most outspoken critics of human rights violations against Afghani women and children and uses her influence to bring global attention to the situation on the ground in Afghanistan, even as a frustrated American military considers relinquishing it to the Taliban. Her story movingly captures the political and cultural moment in Afghanistan, a country caught between the hope of progress and the bitterness of history"-- c Provided by publisher